Why do some societies invent more than others? - Shane, Scott A. (Journal of Business Venturing, 1992)
Having being involved in management operations overseas, many executives have come to the conclusion that cultural differences influence the relative performance of companies in different countries. This managerial gut feeling has been supported by academic research, which has shown that cultural forces influence the strategies and structures that firms use. However, one aspect of this cross-cultural research that has gotten little academic research attention is the relationship between cultural values and the innovativeness and inventiveness of a society. This study examines this relationship. Two aspects of culture should have an influence on inventiveness. The first—the extent to which a society stresses social hierarchy—should decrease inventiveness for a number of reasons. Inventiveness is more likely to occur if a society is less hierarchical since bureaucracy reduces creative activity. Communication enhances invention because much of people's inventive activity requires input from others. In hierarchical societies, there is less communication between superiors and subordinates than in non-hierachical societies. Innovation requires decentralized authority because such a structure brings more information to the attention of the senior managers and gives employees greater incentive, and hierarchical societies tend to have more centralized authority. Hierarchical societies tend to have control systems based less on trust, and more on rules and procedures, and these controls inhibit creativity and inventiveness. Inventiveness is hard work and requires a strong work ethic, and hierarchical societies are more fatalistic and less inclined to undertake the hard work necessary for innovation. Finally, inventions often cause radical social change. Hierarchical societies seek to minimize this change because the redistribution of power that accompanies social change might cause those at the top of the hierarchy to fall. Individualistic societies should be more inventive than collectivistic ones. Individualistic societies value freedom more than collectivistic societies, and freedom is necessary for creativity. Inventiveness requires an outward-looking view. Individualistic societies do not stress loyalty to the extent that collectivistic societies do, so they are able to gather more information necessary for invention. Small firms are more innovative than large ones, and people in individualistic societies tend to prefer small firms, whereas those in collectivistic societies prefer large ones. Inventors need to be compensated for their inventions monetarily and with recognition. This is more likely in individualistic societies, which are more willing to single people out. The support of senior people in organizations is necessary for innovation to occur, and people in individualistic societies are more likely to seek this support. Finally, the psychological characteristics of independence, achievement, and non-conformity, which have been found to encourage innovation, are all more common in individualistic societies. This study examined the per capita number of invention patents granted to nationals of 33 countries in 1967, 1971, 1976, and 1980 and compared it with an index of the values of power distance (social hierarchy) and individualism, compiled from a survey of 88,000 employees at IBM undertaken by Geert Hofstede in the late 1960s and early 1970s. The results showed that individualistic and non-hierarchical societies are more inventive than other societies. The findings have two implications for managers. First, some societies might have a cultural comparative advantage in inventiveness. If this is true, these countries are the best locations for research and development in multinational corporations. Second, the same cultural values that operate on the national level operate on the firm level, leading companies and countries with innovative cultures to invent more than others.